Producción y calidad de la biomasa de Vicia villosa como cultivo de cobertura en el Chaco seco - Prieto Angueira, Salvador; Diez, Josefina; Lopez, Lurdes Andrea; Sauer, Mariana Veronica; Acreche, Martin Moises; Lescano, Marcelo David; Dominguez, Nelson Javier; Lopez Juane, Pablo Alejandro; Berton, Maria Clara (Asociación Argentina Ciencia del Suelo, 2024)
Poster